Optimal Child Allowances with Heterogeneous Fertilities - András Simonovits (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2014)
A child-allowance system is to raise fertility beyond the individual optimum. The more heterogeneous the population with respect to rearing costs, however, the stronger are the redistribution and polarization.
Keywords: J13; 330; Child allowance; Endogenous fertility; Heterogeneous fertility